Epidemiology of uveitis in urban Australia. (2nd May 2019) - Hart, Colby T.; Zhu, Elena Y.; Crock, Carmel; Rogers, Sophie L.; Lim, Lyndell L.
Abstract: Importance: Few prior studies have described the epidemiology of uveitis in the Australian population. Background: To report the incidence and period prevalence of active uveitis in Melbourne and detail their subtypes and aetiologies. Design: Cross‐sectional study using retrospective medical record review in a tertiary hospital. Participants: Patients with a coded diagnosis of uveitis who attended the emergency department or specialist ocular immunology clinic at the Royal Victorian Eye and Ear Hospital between November 2014 through October 2015 (N = 1752). Methods: Medical records were reviewed to confirm the date of diagnosis and subtype of uveitis. Incidence and prevalence rates were calculated utilizing estimates of the adult population residing in areas of greater Melbourne with more than 30 ocular‐related presentations to the emergency department annually. Main Outcomes and Measures: Presence and date of onset, anatomical distribution and aetiology of uveitis. Results: During the study period, 734 new cases of uveitis and 502 cases of pre‐existing uveitis requiring active treatment were confirmed. These figures yielded an incidence of 21.54 (CI 20.03, 23.15) per 100 000 person‐years and a period prevalence of 36.27 (CI 34.30, 38.35) per 100 000 persons. The distribution of prevalent uveitis cases was anterior (75%), intermediate (6%), posterior (15%) and panuveitis (4%). An infectious aetiology accounted for 13.4% of cases, a systemic associated disease for 26.4% of cases, and no cause was identified in 60.2% of cases. Conclusion and Relevance: The incidence and prevalence rates of uveitis in urban Australia were lower than recent studies from the United States and Europe.